An Assessment of Serum Cholesterol level and BMI in Women: Study in Several Private Chambers in Mymensingh (Community Based Medical Journal, 2019)
The increased risk of cardiovascular disease associated with higher serum cholesterol levels in middle-aged persons has been established, but there have been few studies conducted regarding the issues in Mymensingh. For evaluation of serum cholesterol and BMI in women of Mymensingh, across-sectional studywas conducted in several private chambers in the districts of Mymensingh, Bangladesh during the period from January 2017 to December 2017. A total of 48 Female patients participated in the study. In the study, participants were aged between 18 to 29 years of age. The study suggested that the serum cholesterol was below 4.99 were 15(31.25%), 5.00 to 6.49 were 13(26.08%) and above 6.50 were 20 (41.67%), the Mean ± SD was 4.45 (0.76). The health status according to BMI showed that 12.50% (n=6) of the participants were underweight 30. The Mean ± SD was 18.93± (3.68). Measurement of BMI and Serum Cholesterol levels can help doctors to treat patients properly for reducing the burden of death in our country.CBMJ 2019 July: Vol. 08 No. 02 P: 4-9